Effect of UV-B radiation on the photoprotective and antioxidant response in Vaccinium corymbosum L.: An approach to the UV-B resistance mechanisms. - Luengo-Escobar, Ana (2019)
Despite the Montreal protocol success and the eventual recovery of the ozone layer over Antarctica, there are still concerns about increased levels of ultraviolet-B (UV-B) radiation in the Southern Hemisphere. It is expected that the pre-1980 levels of the ozone layer recovery may still require several decades, but this not necessarily will decrease levels of UV-B according to new models that predict increment in the UV-B radiation driven by climate change. UV-B induces physiological, biochemical and morphological stress responses in plants, which are species-specific and different even for closely related cultivars. In woody plant species, understanding of long-term (days) mechanisms to cope with UV-B-induced stress is limited. Therefore, a greenhouse UV-B daily course simulation was performed for 21 days (long–term) with two blueberry cultivars (Legacy and Bluegold) under UV-BBE irradiance of 0, 0.07 and 0.19 Wm−2. Physiological, metabolic and molecular responses of Vaccinium corymbosum (Highbush blueberry) under UV-B radiation as an approach to the UV-B resistance mechanisms were assessed. Cultivars demonstrated to behave differently under simulated UV-B conditions. The main scientific contribution in this context was to find that the UV-B resistant cultivar responds early by metabolism rearrangement compared to the sensitive cultivar. The dynamical use of photoprotective and antioxidant mechanisms to cope with UV-B stress was also demonstrated. Moreover, the resistant cultivar showed to synthesize de novo molecules in response to UV-B (mainly flavonol glycosides). However, when we look at the amount of the main phenylpropanoid compounds and gene expression related to their synthesis, it was found that the resistance mechanism also can be attributed to the intrinsic phenylpropanoid metabolic status of plants. The higher amount of different flavonoid glycosides and the transient induction of UDP flavonoid glycosyltransferase gene (UFGT) can be part of the UV-B resistant mechanism. PFCHA-Becas PFCHA-Becas